PENGARUH PEMBELAJARAN THINK – PAIR – SHARE BERBANTUAN TOPWORKSHEET TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK X SMA NEGERI 1 BANDAR PULAU - Khoirisma Ramadhani; Eva Margaretha Saragih (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
This study was conducted to examine the effect of using LAPS Heuristic-based E-LKPD on students’ learning outcomes. The research applied a quantitative approach with a pretest-posttest design. The sample of this study consisted of 36 students. Data were collected through a pretest administered before the implementation of the E-LKPD and a posttest conducted after the implementation of the LAPS Heuristic-based E-LKPD. The obtained data were analyzed using a paired sample t-test to determine the differences in learning outcomes before and after the treatment. The findings revealed that the average pretest score was 69.36, while the average posttest score increased to 92.47. The statistical analysis showed that the value of , whereas the value of at the 5% significance level. Since the value of was higher than , H₀ was rejected and H₁ was accepted. These results indicate that the use of LAPS Heuristic-based E-LKPD had a significant effect on improving students’ learning outcomes. Therefore, the LAPS Heuristic-based E-LKPD was considered effective for use in the learning process.